THE EFFECTS OF FINANCIAL INCLUSION, BANK-SPECIFIC FACTORS, AND MACROECONOMIC CONDITIONS ON NON-PERFORMING LOANS IN INDONESIA - Muntashir, Muhammad Afif (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose This study aims to determine the influence of financial inclusiveness, bank-specific factors, and macroeconomic conditions on the value of NPL in Indonesia. Design/methodology/approach The method used in this study is dynamic panel data, and the estimation parameter used is the Generalized Method of Moments (GMM) with data from 33 provinces in Indonesia for the period 2013-2023. Findings The results obtained indicate that there is no significant influence of inclusive finance on the NPL value. The LDR has an influence on the NPL but it is not significant. The amount of credit has a positive and significant effect on NPL. PDRB has a positive and significant effect on the value of NPL. Inflation has a negative effect, but it is not significant on NPL. In the long term, the amount of credit and PDRB have a significant effect on NPL in Indonesia Research limitations/implications Financial Services Authority and banks need to strengthen financial inclusion programs by expanding access to services to remote areas and increasing community financial literacy through education and partnerships with local institutions. Banks must also tighten credit risk analysis by implementing data-based technology, such as systems scoring which is effective for borrowers to screen high-risk borrowers Originality/value The novelty in this research is the use of financial inclusion variables Financial Inclusion Index in looking at the impact on non-performing loans in 33 provinces in Indonesia for the period 2013-2023.